A systematic approach to the monitoring of competitive weightlifters - Hornsby, W. G. lll (2013)
Purpose: The purpose of this training, monitoring study was to investigate how alterations in training variables affect changes among underlying mechanisms of performance and weightlifting performance and whether certain variables are better suited for monitoring the training process than others. Additionally, the importance of including barbell displacement in volume load (VL) calculations was investigated. Subjects: Seven (4 males, 3 females) competitive weightlifters participated in the study dealing with alterations of underlying mechanisms and performance while 8 weightlifters (5 males, 3 females) participated in the investigation of exercise displacement. Methods: The weightlifters participated in a 20-week periodized resistance training plan. Measurements of maximal strength and explosive strength from the isometric mid-thigh pull (IMTP) and static jumps (SJ) with 0kg, 11kg, and 20kg were taken toward the end of each training block (weeks 1, 6, 10, 13, 17, and 20). Weightlifting performance was measured at weeks 0, 7, 11, and 20. The detailed monitoring of VL consisted of recording the load, rep count, and with and without displacement for every set for 20 weeks. Results: Very strong correlations were displayed between weightlifting performances and isometric rate of force development (RFD), isometric peak force (PF), and peak power (PP) at 0kg, 11kg, and 20kg. During periods of higher volume loads RFD was depressed to a much greater extent than peak force (PF). For the males, similar to RFD, JH at 20kg responded in a manner fitting an expected fatigue response compared to JH at 0kg and 11kg. VL correlated very strongly to VL with displacement; however, statistically significant differences existed for percent change (4 of the 7 time periods measured) Conclusions: PF is more resistant to volume alterations than RFD and JH at 20kg. Thus RFD and JH at 20kg appear to be superior monitoring metrics. The testing period in which preparedness was the highest happened in concert with a taper. Based on correlations, PF, RFD, and PP are variables on which coaches should focus for enhancing performance. A strong relationship exists between VL and VL with displacement; however, changes from one period to the next are not always the same.